2020
DOI: 10.36351/pjo.v36i1.1007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue Versus Autologous Serum for Conjunctival Autograft Fixation in Pterygium Surgery

Abstract: Purpose:  To compare the outcomes of conjunctival autograft fixation using autologous serum vs fibrin glue to cover the bare sclera in pterygium excision surgery. Study Design:  Quasi experimental study. Place and Duration of Study:  The study was conducted in Ophthalmology Department of CMH Kharian from April 2018 to November 2018. Material and Methods:  Forty patients with primary pterygium were selected by convenient sampling technique. Patients with recurrent Pterygia and moderate to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…The recurrence rate in our patients (8%) is comparable to that of CAG andAMT. [4][5][6] The rate of significant post-operative flap edemain our study (5.5%), was lesser than that reported by Shakil et al (16.6%) probably because the pedicle size of our flap was larger compared to anchored RCF,ensuring better flap vascularity and stability, and preventing significant reperfusion injury. Re-perfusion injury is more common in free flap or graft than pedicled flap as restoration of blood supply to the former takes more time.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The recurrence rate in our patients (8%) is comparable to that of CAG andAMT. [4][5][6] The rate of significant post-operative flap edemain our study (5.5%), was lesser than that reported by Shakil et al (16.6%) probably because the pedicle size of our flap was larger compared to anchored RCF,ensuring better flap vascularity and stability, and preventing significant reperfusion injury. Re-perfusion injury is more common in free flap or graft than pedicled flap as restoration of blood supply to the former takes more time.…”
Section: Discussioncontrasting
confidence: 50%
“…19 Studies done in our population show recurrence rate following CAG, AMT and conjunctival flap varying from 3.3% to 25%, 7.84% to 10% and 6.6% to 9.76% respectively. [4][5][6]22,23 Shakil et al used anchored conjunctival flap technique in which flap was anchored at 1mm frill of limbal conjunctiva and secured at scleral bed with 7/0 polyglactin (vicryl) sutures. The author found this method resulting in lesser postoperative edema and similar recurrence rates compared to CAG, 22 while Akhter et al reported shorter surgical time with flap compared to CAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted in eight eyes (40%) in group A treated with fibrin glue and one eye (5%) in group B treated with autologous serum. 13 It has been known that thick grafts not covering the limbus may increase the risk of recurrence. 14 Sabahattin Sul et al, used autologous serum drops in pterygium surgery.…”
Section: Discussionmentioning
confidence: 99%